Modifkasi Materi Praktikum (Karbohidrat-Enzim) Untuk Meningkatkan Pemahaman Konsep Biokimia Secara Komprehensif dan Efsien - Titik Wijayanti; Purwaning Budi Lestari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2016)
Main objectives of this research are to analyze the increase in understanding biochemistry concepts comprehensively caused by practice concept modifcation (Carbohydate-Enzyme) and analysis the effciency of practical activities caused by practice concept modifcation (Carbohydate-Enzyme). Research conducted in September through November 2015 are analytical descriptive research, there are 80 students as respondents were devided into 2 groups of treatment, namely group A as group with practice module that has not been modifed and group B with practice module that have been modifed. Paired t test result showed that group with practice module were modifed to get the score of post-test evaluation better and signifcantly different than group with practice module that has not been modifed. The validation result of practice module by students, instucture, material experts and media experts showed that practice module modifed is eligible to used as practical module in the future.